PENGARUH KESESUAIAN KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI (Studi Empiris Pegawai Perusahaan Manufaktur Provinsi Lampung) - Dian Mustika; Fitri Agustina; Yaumil Khoiriyah (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2023)
The study was conducted with the aim of analyzing the effect of compensation suitability, and organizational culture on employee performance of Manufacturing Company in Lampung Province. This research is a quantitative study using the sampling technique used in this study is probability sampling using simple random sampling combined with purposive sampling, the survey method uses a questionnaire as a data collection medium distributed via google form to all employees of Manufacturing Company in Lampung Province with a sample size obtained as many as 112 participants. The data analysis and hypothesis testing method used is Structural Equation Modeling (SEM) using WrapPls 7.0 software analysis tool. The results of this study indicate that compensation suitability, and organizational culture have a positive effect on employee performance of Manufacturing Company in Lampung Province.